STUDI KARAKTERISTIK KAMPAS REM KENDARAAN PENUMPANG TYPE OES (ORIGINAL EQUIPMENT SPAREPART) DAN AM (AFTER MARKET) PADA DRY DAN WET SLIDING - Rovilla Kennedy; Eko Surojo; Wijang Wisnu Raharjo (Mekanika: Majalah Ilmiah Mekanika, 2019)
Brake pad is one of the components of a motor vehicle which is served to slow or stop the rate of vehicle. The brake pad of automotive vehicle on the market is divided into three types that are an OEM (original equipment manufacturer), OES (original equipment spare parts) and AM (aftermarket). The brake pad operates under various conditions of dry or wet sliding. The majority of researchers investigated brake pad characteristic on dry sliding. Studies of wet braking behavior are rare in the tribology literature. Therefore, this research performed testing of friction characteristics of dry and wet sliding by using brake pad type OES and AM on a passenger vehicle. Each brake pad tested using the machine pin on disc tribometer type and observed using SEM. The result showed that the brake pad type OES has a good stability on testing dry sliding and wet sliding. In addition, passenger type brake pad OES has specific wear low so more durable in used. Meanwhile the results of SEM showed that the friction layer were not formed during wet sliding.